3D printed clamps improve spine specimen fixation in biomechanical testing. (2nd January 2020) - Cornaz, Frédéric; Fasser, Marie-Rosa; Spirig, José Miguel; Snedeker, Jess G.; Farshad, Mazda; Widmer, Jonas
Abstract: This study presents an anatomically customizable fixation technique for biomechanical spine experiments using a 3D printed clamping system. The aim of this study is to evaluate the feasibility and compare the fixation rigidity of the novel technique to PMMA potting with and without screw augmentation. For this purpose, 16 thoracic and lumbar functional spine units of bovine, porcine, ovine and human cadavers (4 each) were consecutively fixed with all three techniques and loaded in six degrees of freedom. The combined relative movement between the cranial and caudal vertebral body and their corresponding fixtures were recorded using a 3D motion capture system. The 3D printed clamps did provide multiple advantages, showed no failures and the fixation rigidity was superior to potting in all loading directions and superior to screw-augmented potting in two of six loading directions (p < 0.05). In conclusion, the here proposed novel fixation method showed equal to superior properties in comparison to both other methods used in this study. When considering all characteristics of 3D printing, 3D printed fixtures can be an effective alternative to potting.